Strategi Menyanyi Meningkatkan Daya Ingat Siswa pada Istilah IPA Sistem Tata Surya SMP: The Singing Strategy for Enhancing Student Memory of Solar System Science Terminology in Junior High School - Lestari, Widy Dwi (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to describe the implementation of a singing strategy in science education and to analyze its influence on enhancing student memory of scientific terms within the solar system unit. The primary issue addressed is the low ability of seventh-grade students to comprehend and recall abstract and technical science terminology. This research employed a qualitative approach using a case study method conducted in a seventh-grade class at Bani Taqwa Junior High School during the 2024/2025 academic year. Data collection techniques included participatory observation, in-depth interviews with the teacher and students, and documentation of learning activities. The findings indicate that the singing strategy positively impacted the students' learning process by increasing enthusiasm, active engagement, and motivation. Songs, structured according to the conceptual sequence of the solar system, helped students remember scientific terms through rhythmic repetition, which supports the formation of long-term memory. This strategy fostered a fun and interactive learning atmosphere, leading to improved student focus and participation. The study concludes that the singing strategy is an innovative and effective approach for helping students understand and remember science concepts. It is recommended as an alternative teaching method for science material containing technical and abstract terms.